Describing spoken English - Kreidler, Charles W., 1924- (London ; New York : Routledge, 1997)
The pronunciation of English. Speech. The structure of language. English consonants. English vowels. Syllables. Strong and weak syllables. Word stress. Stress in compound words and phrases. The role of accent in discourse. Intonation. Morphemes that vary in form.
Keywords: English language; Linguistics; English language -- Spoken English; English language -- Variation